Analisis Faktor-Faktor Preferensi Konsumen Dalam Menggunakan E-Commerce Tokopedia - Naqiyatus Sholahah; Nurhadi Nurhadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In this modern era, with the existence of internet, which are followed with it’s using activity of them. One of those is the business activities called “e-commerce”. There are several e-commerce platforms in Indonesia, but in 2021 Tokopedia become the number one e-commerce platform in Indonesia. In this study, primary data was used by distributing questionnaires to Tokopedia e-commerce users in the Gresik area. The research population is Tokopedia e-commerce consumers in the Gresik area with easy users using purposive sampling technique with a total of 385 respondents. This research uses 17 manifest variables that have been matrixed with exploratory factor analysis techniques. In the final calculation of the exploratory factor analysis, 3 main factors were found that became consumer preferences in using Tokopedia e-commerce, namely the first factor are efficiency (Easy to Operate Features, Complete Features, Attractive Menu Interface, Easy Payment, Various Products, Ease of Finding Products , Easy Payment Mechanisms, Fast Payment Processes, Easy Applications to Use Anytime), the second factor are Facilities and Security (Easy to Use Anywhere Applications, Offered Cashback Promos, Free Shipping Promos, Verification Via Email/Mobile Number, Double Verification When Payments, and Account Verification Using Ktp), the third factor are promotion (Popular Celebrity Endorser and Advertising in Media) with a cumulative value of 65.812, so the KMO key and Measure Sampling Adequacy (MSA) have met the requirements. Keywords : Preferences, Factor Analysis, E-Commerce, Tokopedia,